Welcoming Spaces, Welcoming Environments: Addressing Bias and Over-Policing in Libraries. Issue 8 (17th November 2021) - Lipinski, Brent; Saunders, Nesha
Abstract: This article explores how the creation of holistic and welcoming spaces is critical to delivering empathy-driven library services. We discuss how libraries can address barriers that—intentionally or unintentionally—result in spaces that are not equal and just for all, and are instead punitive We suggest reassessing policies, physical security measures, and staffing procedures. We call on library administrators to listen to their communities, especially regarding what kind of security measures and policies actually create trusted safe libraries. By being open to change, we can avoid the biased mistakes of the past and make our facilities truly a welcoming community space for our patrons.